2010
DOI: 10.1016/j.febslet.2010.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Roles of GPR41 and GPR43 in leptin secretory responses of murine adipocytes to short chain fatty acids

Abstract: a b s t r a c t GPR41 is reportedly expressed in murine adipose tissue and mediates short chain fatty acid (SCFA)-stimulated leptin secretion by activating Ga i . Here, we agree with a contradictory report in finding no expression of GPR41 in murine adipose tissue. Nevertheless, in the presence of adenosine deaminase to minimise Ga i signalling via the adenosine A1 receptor, SCFA stimulated leptin secretion by adipocytes from wild-type but not GPR41 knockout mice. Expression of GPR43 was reduced in GPR41 knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
251
6
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 297 publications
(266 citation statements)
references
References 18 publications
5
251
6
4
Order By: Relevance
“…It was found that leptin secretion from wild-type adipocytes was increased by acetate, yet butyrate had no significant effect (35) . Owing to the different activation potencies of FFAR2 and FFAR3 to acetate (29,30) , this would imply that FFAR2 is responsible for triggering leptin secretion.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that leptin secretion from wild-type adipocytes was increased by acetate, yet butyrate had no significant effect (35) . Owing to the different activation potencies of FFAR2 and FFAR3 to acetate (29,30) , this would imply that FFAR2 is responsible for triggering leptin secretion.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…Both FFAR2 and FFAR3 are activated by physiological concentrations of SCFA, although a preference of FFAR2 for acetate and propionate and of FFAR3 for propionate and butyrate has been reported (29)(30)(31) . These receptors have been shown to be expressed not only in the gut epithelium (32,33) where SCFA are produced and are at their highest concentrations, but also at multiple tissue sites, including adipose tissue (34)(35)(36) , immune cells (29) , skeletal muscle (31) and within the peripheral nervous system (37,38) . A possible role for these receptors in energy intake regulation emerged with the identification that FFAR2 and FFAR3 are present on colonic endocrine L-cells (32,33) .…”
Section: Scfa Receptors and Anorectic Gut Hormone Releasementioning
confidence: 99%
See 1 more Smart Citation
“…De plus, GPR43 est exprimé par les polynucléaires neutrophiles et éosinophiles [7,36], et les souris dont le gène gpr43 est invalidé ont un profil inflammatoire [37]. L'expression de GPR43 est aussi détectable dans les adipocytes blancs [38], mais celle de GPR41 reste controversée [39]. Diverses publications suggèrent que ces récepteurs jouent un rôle dans la régulation de l'adipogenèse [38], la lipolyse [40] et la sécrétion de leptine [39] par les adipocytes.…”
Section: Gpr41 Et Gpr43unclassified
“…L'expression de GPR43 est aussi détectable dans les adipocytes blancs [38], mais celle de GPR41 reste controversée [39]. Diverses publications suggèrent que ces récepteurs jouent un rôle dans la régulation de l'adipogenèse [38], la lipolyse [40] et la sécrétion de leptine [39] par les adipocytes. Ximenes et al [41] ont par ailleurs montré que l'acide propionique, un ligand de GPR41 et GPR43, inhibe la sécrétion d'insuline en réponse au glucose dans les îlots de rats.…”
Section: Gpr41 Et Gpr43unclassified